VLADIMIR SKALICKA AND LANGUAGE CONTACT - Bocek, Vit (Bohemica Olomucensia, 2022)
The paper maps the view of Vladimir Skalicka, one of the main figures of the second generation of the Prague School, on the four related questions of language convergence and contact (linguistic areas, mixing of languages and dialects, causes of linguistic change, and borrowing). Skalicka's ideas on language contact are presented in the context of his work, especially his typological theory and his approach to the question of language development. Also discussed and evaluated is the place that Skalicka's thinking on language contact has in a wider context, namely in the Prague School. It is shown that these are not antiquated opinions but a living heritage that can be further developed.
Keywords: Vladimir Skalicka; typology; language contact; borrowing; linguistic area; Prague School